LEGAL CONSEQUENCES RELATED TO NON-NOTARY BINDING SALE AND PURCHASE AGREEMENTS (PPJB) ON LEGAL CERTAINTY IN LAND SALE AND PURCHASE TRANSACTIONS (CASE STUDY NUMBER 31/Pdt.G/2024/PN Sbr) - Simbolon, Mario; Putra, Rayhan Prakasa; Hakim, Imam Al; Pancaksi, Aditya Wira (Ann Publisher, 2025)
Abstract. Background. PPJB or Sale and Purchase Binding Agreement is a legal tool used for land purchase and sale transactions in Indonesia. With the existence of PPJB, the parties get the opportunity to bind the initial agreement before officially implementing the Deed of Sale and Purchase (AJB) in front of the Land Deed Making Officer (PPAT). Aims. This study examines the legal consequences of Non-Notarial and Notarial Sale and Purchase Binding Agreements (PPJB) in land sale transactions in Indonesia. Despite its frequent use, Non-Notarial PPJB has legal weaknesses, particularly in terms of evidentiary strength. Conversely, Notarial PPJB is considered stronger legally, as it is an authentic deed recognized under Article 1870 of the Indonesian Civil Code (KUHPerdata). Methods. Through Case Study No. 31/Pdt.G/2024/PN Sbr, this research identifies that in disputes, judges tend to favor parties holding Notarial PPJBs, which are viewed as more compliant with formal legal requirements. Result. The findings suggest that Notarial PPJB offers higher legal certainty and minimizes the potential for disputes. Hence, society must know the legal consequences of using PPJB in land sale transactions. Additionally, increasing public awareness and education regarding the importance of Notarial PPJB is recommended as a means of optimal legal protection. Conclusion. This emphasizes the importance of public understanding of legal aspects in preparing PPJB, especially in land purchase and sale transactions that involve significant economic value and have the potential for complex legal conflicts. Implementation. PPJB notarial is highly recommended to minimize the risk of future disputes and provide more optimal legal protection for all parties involved. It is hoped that the government can increase socialization about the importance of notarial PPJB and provide education about the legal risks that may arise from using non-notarial PPJB.